Crop Harvesting-Related Soil Loss in Tanzania’s Usambara Mountains: The Case of Carrot, Onion, and Potato - Winnie; Mary El-Waki (Global Journal of Plant and Soil Sciences, 2025)
Soil losses from root, tuber, and bulb harvesting are among the many soil erosion processes that pose a danger to sustainable agriculture, although they are not well studied, especially in tropical regions. Thus, a study on acrisols and fluvisols in Tanzania's Western Usambara Mountains was carried out in two communities with dissimilar agro-ecological circumstances. Investigating the mass of nutrients and soil lost as well as the variables affecting variations in soil loss due to crop harvesting (SLCH) for potatoes (Solanum tuberosum L.), onions (Allium cepa L.), and carrots (Daucus carrota) under minimal input agriculture was the goal. Soil losses from root, tuber, and bulb harvesting are among the many soil erosion processes that pose a danger to sustainable agriculture, although they are not well studied, especially in tropical regions. Thus, a study on acrisols and fluvisols in Tanzania's Western Usambara Mountains was carried out in two communities with dissimilar agro-ecological circumstances. Investigating the mass of nutrients and soil lost as well as the variables affecting variations in soil loss due to crop harvesting (SLCH) for potatoes (Solanum tuberosum L.), onions (Allium cepa L.), and carrots (Daucus carrota) under minimal input agriculture was the goal. Soil losses from root, tuber, and bulb harvesting are among the many soil erosion processes that pose a danger to sustainable agriculture, although they are not well studied, especially in tropical regions. Thus, a study on acrisols and fluvisols in Tanzania's Western Usambara Mountains was carried out in two communities with dissimilar agro-ecological circumstances. Investigating the mass of nutrients and soil lost as well as the variables affecting variations in soil loss due to crop harvesting (SLCH) for potatoes (Solanum tuberosum L.), onions (Allium cepa L.), and carrots (Daucus carrota) under minimal input agriculture was the goal. Soil losses from root, tuber, and bulb harvesting are among the many soil erosion processes that pose a danger to sustainable agriculture, although they are not well studied, especially in tropical regions. Thus, a study on acrisols and fluvisols in Tanzania's Western Usambara Mountains was carried out in two communities with dissimilar agro-ecological circumstances. Investigating the mass of nutrients and soil lost as well as the variables affecting variations in soil loss due to crop harvesting (SLCH) for potatoes (Solanum tuberosum L.), onions (Allium cepa L.), and carrots (Daucus carrota) under minimal input agriculture was the goal. Soil losses from root, tuber, and bulb harvesting are among the many soil erosion processes that pose a danger to sustainable agriculture, although they are not well studied, especially in tropical regions. Thus, a study on acrisols and fluvisols in Tanzania's Western Usambara Mountains was carried out in two communities with dissimilar agro-ecological circumstances. Investigating the mass of nutrients and soil lost as well as the variables affecting variations in soil loss due to crop harvesting (SLCH) for potatoes (Solanum tuberosum L.), onions (Allium cepa L.), and carrots (Daucus carrota) under minimal input agriculture was the goal.